DAMPAK COVID-19: GURU MENGADOPSI MEDIA SOSIAL SEBAGAI E-LEARNING PADA PEMBELAJARAN JARAK JAUH - Mohammad Salehudin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The purpose of this study was to find out how teachers as users of social media adopted it into e-learning in distance learning (PJJ) due to the impact of co-19. This research uses a quantitative approach with a survey method. The instruments in this study used a valid instrument from UEQ which was translated into Indonesian, which has 6 scales and 26 items, submitted in digital form via Google form. Participants in this study were 43 PAI teachers chosen randomly. This research describes a descriptively quantitative mean, variance, and standard deviation values. The results found each of the six scales was Attractiveness with a mean value of 1.73 being in the Good benchmark category, Perspicuity 1.56 Above Average, Efficiency (Efficiency) ) 1.87 Excellent, Dependability 1.42 Above average, Stimulation 1.86 Excellent and Novelty 1.34 Good. The conclusion was drawn that teachers as users of social media who were adopted into e-learning at PJJ when the pandemic Covid-19 Indonesia was above good grades and even excellent. It can be said that the PAI teacher has the ability to use good social media even excellent (very well) which he adopted as e-learning in PJJ.